Synthesis and Characterization of Some New Oxazol, Thiozol, Oxazolidinone Derivatives from Quinazoline - Nagham Majid Abdulhassan (Journal of Global Pharma Technology, 2018)
Quinazolinones are interesting materials because of their valuable biological effects. In this study some new 2, 3-disubstituted-4(3H) quinqzolinone derivatives were synthesized from anthranilic acid in six steps by introducing a new chiral center to the aliphatic side chain of the quinazolinone. In the last step, cyclization with ethyl chloro acetate and 4-phenyl-phenacyl bromid moiety afforded final compounds. The structures of compounds were confirmed by F IR, 1HNMR and.Keywords: Anthranilic acid, 4(3H)-Quinazolinone, Synthesis.